Arabic Language Sciences, Literature and Arts in Al- Maghreb and Al-Andalus through Ibn Khaldun’s “Muqaddema” - Amer A. Qobbaj (Journal of Arts and Social Sciences, 2017)
This study aims to identify and portray the main historical and civilizational features of the linguistic situation in Al-Maghreb and Al-Andalus, based on the Muqaddema of Ibn Khaldun (d. 808 A.H\1406 A.D), who was a witness to many of the scientific aspects of civilization in both countries, especially the Arabic language sciences, literature and arts, a large bulk of which, was transferred from the Islamic East and reached Al-Andalus and Al- Maghreb. Ibn Khaldun had divided sciences into two groups: sciences based on textual evidence and sciences based on cognitive reasoning. He considered the Arabic Language sciences within the textual sciences, linking their emergence and wide spread to two reasons: “Umran” (urbanism, culture and civilization), and continuity in the transmission of knowledge from one generation to another in major cities, especially before the destruction of Kairouan by Hilali tribes during the fifth century A.H./eleventh century AD, and before the fall of Cordoba by Spaniards during the seventh A.H century/thirteenth A.D century. Despite the fact that Ibn Khaldoun was pessimistic about the condition of learning and knowledge in his era, particularly the deteriorating condition of the Arabic language caused by the mixing of Arabs with non-Arabs, he mentioned in Muqaddimah many scholars who maintained and protected the Arabic language and spread it in Al-Maghreb and Al-Andalus through their published books in various areas of Arabic syntax, linguistics, semantics, and poetry. These books constituted and shaped the cultural, educational and Islamic identity. Much research has been done in the area of Arabic linguistics, mainly in Al-Maghreb and Al-Andalus, yet most of it did not analyze the contents of the Muqaddema which relate to Arabic language in these two areas. This study investigates the linguistic references in the Muqaddema about the Arabic language and shed some light on the features of the historical relationships between these two regions of the Western Islamic world, as well as the mutual interaction that accompanied the linguistic development there.